ATTITUDE OF INDIAN MOTHERS TOWARDS CHILD RIGHTS - Shanmugam, Valliammal; Ramachandra, , (European Scientific Journal, ESJ, 2014)
Children form a very important population in any society. The future health status and behaviour of a person are laid down during childhood. To ensure survival and healthy development into adulthood, proper care during childhood should address all the basic needs for children. Child care is mostly the responsibility of mothers. There are very few population based data on attitude of mothers on child rights in South India. The attitude of the mothers towards child rights is very important as they are the basic unit in rearing children. This study was therefore carried out among mothers at selected paediatric Outpatient department of South India. The aim of the study was to assess attitude of mothers towards child rights of selected dimensions. An exploratory research design was adopted to accomplish the purpose of this study. The simple random sampling technique was used to select 40 mothers. The data was collected for a period of 10 days. Each day four subjects were interviewed. Modified Children's Rights Attitude Scale developed by Rogers and Wrightsman (1978) semi structured four point Likert scale on Child Rights was used as main screening instrument. It contained 25 items. The results revealed that the mean attitude score of the subjects was (69.30) with mean percentage of (69.3%). Majority of the subjects (92.5%) had moderately favourable attitude towards child rights. A significant association was found only between attitude score and residential status of the mothers (X2= 7.544, P< 0.05).